Circulating Cell-Free Mitochondrial DNA in Cerebrospinal Fluid as a Biomarker for Mitochondrial Diseases - Trifunov, Selena; Paredes-Fuentes, Abraham J; Badosa, Carmen; Codina, Anna; Montoya, Julio; Ruiz-Pesini, Eduardo; Jou, Cristina; Garrabou, Glòria; Grau-Junyent, Josep M; Yubero, Dèlia; Montero, Raquel; Muchart, Jordi; et al. (Clinical chemistry (Baltimore, Md.), 2021)
Abstract Background Mitochondrial diseases (MD) are genetic metabolic disorders that impair normal mitochondrial structure or function. The aim of this study was to investigate the status of circulating cell-free mitochondrial DNA (ccfmtDNA) in cerebrospinal fluid (CSF), together with other biomarkers (growth differentiation factor-15 [GDF-15], alanine, and lactate), in a cohort of 25 patients with a molecular diagnosis of MD. Methods Measurement of ccfmtDNA was performed by using droplet digital PCR. Results The mean copy number of ccfmtDNA was approximately 6 times higher in the MD cohort compared to the control group; patients with mitochondrial deletion and depletion syndromes (MDD) had the higher levels. We also detected the presence of both wild-type mtDNA and mtDNA deletions in CSF samples of patients with single deletions. Patients with MDD with single deletions had significantly higher concentrations of GDF-15 in CSF than controls, whereas patients with point mutations in mitochondrial DNA presented no statistically significant differences. Additionally, we found a significant positive correlation between ccfmtDNA levels and GDF-15 concentrations (r = 0.59, P = 0.016). Conclusion CSF ccfmtDNA levels are significantly higher in patients with MD in comparison to controls and, thus, they can be used as a novel biomarker for MD research. Our results could also be valuable to support the clinical outcome assessment of MD patients.